L∞-error estimate for a system of elliptic quasivariational inequalities - M. Boulbrachene; M. Haiour; S. Saadi (International Journal of Mathematics and Mathematical Sciences)
We deal with the numerical analysis of a system of elliptic quasivariational inequalities (QVIs). Under W2,p(Ω)-regularity of the continuous solution, a quasi-optimal L∞-convergence of a piecewise linear finite element method is established, involving a monotone algorithm of Bensoussan-Lions type and standard uniform error estimates known for elliptic variational inequalities (VIs).